Western Theories, Queer Possibilities, Polish Reality. Or, Do We Need Queer Political Theory? Западни теории, квир можности, полска стварност. Или, имаме ли потреба од квир политичка теорија? - Kulpa, Robert; Janeva, Kalina (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Robert Kulpa | Роберт Кулпа Title (English): Western Theories, Queer Possibilities, Polish Reality. Or, Do We Need Queer Political Theory? Title (Macedonian): Западни теории, квир можности, полска стварност. Или, имаме ли потреба од квир политичка теорија? Translated by (English to Macedonian): Kalina Janeva | Калина Јанева Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 9-36 Page Count: 27 Citation (English): Robert Kulpa, “Western Theories, Queer Possibilities, Polish Reality. Or, Do We Need Queer Political Theory?,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008): 9-36. Citation (Macedonian): Роберт Кулпа, „Западни теории, квир можности, полска стварност. Или, имаме ли потреба од квир политичка теорија?“, превод од англиски Калина Јанева, Идентитети: списание за политика, род и култура, т. 6, бр. 2-3 (лето 2007 - зима 2008): 9-36.